Citizens of London: The Americans who Stood with Britain in its Darkest, Finest Hour. (March 2016) - Waters, Christopher
Abstract : Citizens of London: The Americans who Stood with Britain in its Darkest, Finest Hour. By Lynne Olson (Melbourne: Scribe, 2015), pp. xxi + 419. AU27.99 (pb).